Overuse Injury and Its Association with Possible Identified Risk Factors In College Athletes: a Pilot Study - Nawanto Agung Prastowo; Ignatio Rika Haryono (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2023)
Participating in sporting competitions exposes college students to body collisions and complex movements, leading to a higher risk of musculoskeletal injury. If not appropriately treated, acute injuries could evolve into overuse injuries. It can interfere with student activities and academic performance. This study aimed to investigate the overuse injury rate and its association with possible identified risk factors in college athletes. This study is a cross-sectional study involving 100 college athletes from four different sports, including badminton (26 athletes), basketball (21 athletes), futsal (30 athletes), and volleyball (23 athletes). The injury rate was presented as a number of injuries/1000 athletes-exposure (A-E) and 1000 hour-exposure. Possible identified risk factors, gender, age, body mass index (BMI), sports type, and activity were documented. Data on injury rate and student identity were obtained using a questionnaire. Weight and height were measured. Chi-square was applied to analyze the relationship, while binary logistic regression was used to estimate the magnitude of the risk of overuse injury using a reference value. Significance was determined at p0.05. The incidence of overuse injury was 26.2% of all injuries (28 cases). The overall injury rate was 2.58/1000 A-E or 1.41 1000 h-exposure. According to A-E exposure, the highest overuse injury rate was in basketball (3.97/1000 A-E), while the lowest (1.8/1000 A-E) was in futsal. Meanwhile, based on 1000 h-exposure, volleyball was the highest (2.17/1000 h-exposure) and badminton was the lowest (0.85/1000 h-exposure). The overuse injury was mainly found in the lower limb (53.6%). No possible identified risk factors were found to have a relationship with overuse injury (gender, p=0.922; age, p=0.344; BMI, p=0.223; sport type (contact/non-contact), p=0.983; sport type (team/individual), p=0.364; and circumstance (training/competition), p=0.325). The overuse injury rate in college athletes varies depending on the type of sport, with the lower limb being the most affected site. No association was found between possible identified risk factors and overuse injury.